Investigation of deaths by undefined causes: strategy for strengthening health surveillance - Cristina Helena Camurça Correia Pinto; Maria Glêdes Ibiapina Gurgel; Maria Dalva Santos Alves; Maria Leonice de Lima Passos; Selma Antunes Nunes Diniz; Maria Rodrigues da Conceição (Rev Rene)
Cross-sectional and descriptive study, with quantitative approach, was also performed, whose data were collected from the Mortality Information System. From 2003 to 2008 a significant reduction in undefined causes in death certificates was found. In 2007 and 2008, most deaths from undefined causes were processed in the Death Verification Service; concentrated in the age group over 50 years of age and occurring at home. It was concluded that the most accurate information of the cause of death stated in death certificates, permits a reflection and planning of the practice of nurses and other professionals, managers and social control, because it permits the design of epidemiological indicators of health status, crucial subsidy in decision process and in the performance of public health policies.